Glacial inception through rapid ice area increase driven by albedo and vegetation feedbacks - M. Willeit; R. Calov; S. Talento; R. Greve; R. Greve; J. Bernales; V. Klemann; M. Bagge; M. Bagge; A. Ganopolski (Climate of the Past, 2024)
We present transient simulations of the last glacial inception using the Earth system model CLIMBER-X with dynamic vegetation, interactive ice sheets, and visco-elastic solid Earth responses. The simulations are initialized at the middle of the Eemian interglacial (125 kiloyears before present, ka) and run until 100 ka, driven by prescribed changes in Earth's orbital parameters and greenhouse gas concentrations from ice core data.